2018
DOI: 10.1111/ejh.13102
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose Bendamustine‐EAM followed by autologous stem cell rescue results in long‐term remission rates in lymphoma patients, without renal toxicity

Abstract: BendaEAM seems to be feasible with a promising response rate and acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
(50 reference statements)
4
16
0
Order By: Relevance
“…20 In the present study no patients died due to renal toxicity, and the majority of the ARF cases were reversible, as has been previously reported. 16,17,26,27 Identifying factors that indicate patients at risk of ARF such as age over 55 years, a history of previous ARF and the use of concomitant nephrotoxic drugs could stratify patients for ARF risk and adapt supportive care strategy. 20,28 Furthermore, 47% of patients presented with grade III-IV mucositis, which is more frequent than in previous studies on the BEAM regimen.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…20 In the present study no patients died due to renal toxicity, and the majority of the ARF cases were reversible, as has been previously reported. 16,17,26,27 Identifying factors that indicate patients at risk of ARF such as age over 55 years, a history of previous ARF and the use of concomitant nephrotoxic drugs could stratify patients for ARF risk and adapt supportive care strategy. 20,28 Furthermore, 47% of patients presented with grade III-IV mucositis, which is more frequent than in previous studies on the BEAM regimen.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…Interestingly, a study conducted by Noesslinger et al found that the majority of patients (33/41) experienced a rise in creatinine within a few days of bendamustine administration. Unlike other studies, no therapeutic intervention was required for any of the patients 14 . However, BeEAM-related nephrotoxicity has been demonstrated to have more severe consequences.…”
mentioning
confidence: 97%
“…Creatinine elevations after bendamusine-containing HDCT administration has led to concerns over renal toxicity. Several studies have documented nephrotoxicity related to BeEAM chemotherapy, ranging from clinicallyinsignificant creatinine rises to dialysis necessitation 6,8,[14][15][16][17] . Interestingly, a study conducted by Noesslinger et al found that the majority of patients (33/41) experienced a rise in creatinine within a few days of bendamustine administration.…”
mentioning
confidence: 99%
“…Second, at least two controlled phase II studies 2,3 and one retrospective experience 4 on Benda-EAM prior to ASCT were recently published ( Table 1). Only the retrospective, French study 4 reported a high rate of grade ≥ III ARF.…”
Section: Benda-eam Prior To Asct and Renal Toxicity: Much Ado About Nmentioning
confidence: 99%